Language and its importance in interactions for a non-sexist education - Mery Rodríguez Parra; Gloria Peláez Elizalde (Saberes Educativos, 2018)
This article raises the need to highlight the category of gender as a fundamental component in the context of educational action. It consider, specifically, the importance of language in the representation of reality learned by students and taught by teachers, whose framework to their pedagogical practice is given by curricular bases and study programs that invisibilizes the problem of gender and reproduce relations of inequity and exclusion. Hence, the need for a cultural change based on the incorporation of a non-sexist language in educational contexts to thereby promote equitable and inclusive relations.